Synergic Effect of Catalyst/Binder in Passivation Side-Products of Li-Oxygen Cells - Aguirre-Quintana, M; Aguirre-Quintana, M; Herrera-Diaz, F; Herrera-Diaz, F; Márquez-Mandiola, P; Márquez-Mandiola, P (Springer, 2019)
While used in minor proportion respect to other components in cathode formulations, binders play a crucial role in lithium batteries cathode. This is particularly true in Li-O2 batteries which represent a very harsh environment mainly because of the formation, upon cycling, of very aggressive superoxide radicals. In such batteries, the use of catalyst in the cathode formulation is quite usual to help oxygen reduction reaction and oxygen evolution reaction (ORR and OER) to proceed rapidly and reversibly. However, the slightest binder degradation upon cycling can hinder the catalyst effects dramatically, modifying them to act on other reactions associated with the generated side-products, thus deteriorating cell performances and preventing researchers from drawing the right conclusions about catalytic properties of new materials. In this work, the influence of different catalysts in the degradation of the PVDF binder, on the performance of Li-O2 batteries, was investigated. The results obtained were compared with the ones of cathodes prepared with the same catalysts but Li-Nafion binder instead (already reported as stable), to further demonstrate that the choice of binder must be strongly linked to the nature of the catalyst. The catalysts employed for this study were α-MnO2, and commercial Co3O4, and Co phthalocyanines (CoPc). © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.